Strategi Pemerintah dalam Meningkatkan Partisipasi Masyarakat Terhadap Penanganan Covid-19 (Studi di Kecamatan Wonggeduku Kabupaten Konawe): Government Strategy in Increasing Public Participation in Handling Covid-19 [Study in Wongeduku District, Konawe Regency] - Mistika Nirwana Sari; Edy Tadung; Andi Muh. Dzul Fadli (JOURNAL OF GOVERNMENT SCIENCE, 2022)
The Indonesian government currently prioritizes village development as the village law places villages at the forefront of development. Villages are given sources of funds through ADD scheme (Village Fund Allocation) and the authority to manage themselves so as to improve community welfare. In managing village fund sources, the government issued a policy to implement Village Financial System Application (SISKEUDES). The SISKEUDES is an application developed by the Financial and Development Supervisory Agency (BPKP) in order to improve the quality of village financial governance. The basis for the government to make a village fund application is Law No 6/2014 on Village, wherein villages are given the opportunity to pay the costs of routine administration, expenditures, and development programs to improve the welfare and quality of life of the village community. Since the management of ADD is prone to manipulation, SISKEUDES is considered capable of providing positive impact in managing village funds efficiently and appropriately, thus considerably contributing to the creation of a transparent and accountable village fund management system.